What is the Impact of Increased Business Competition? - Felix, Sonia; Maggi, Chiara (Washington, D.C. : International Monetary Fund, 2019)
This paper studies the macroeconomic effect and underlying firm-level transmission channels of a reduction in business entry costs. We provide novel evidence on the response of firms' entry, exit, and employment decisions. To do so, we use as a natural experiment a reform in Portugal that reduced entry time and costs. Using the staggered implementation of the policy across the Portuguese municipalities, we find that the reform increased local entry and employment by, respectively, 25% and 4.8% per year in its first four years of implementation. Moreover, around 60% of the increase in employment came from incumbent firms expanding their size, with most of the rise occurring among the most productive firms. Standard models of firm dynamics, which assume a constant elasticity of substitution, are inconsistent with the expansionary and heterogeneous response across incumbent firms. We show that in a model with heterogeneous firms and variable markups the most productive firms face a lower demand elasticity and expand their employment in response to increased entry.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet